A protective effect of breastfeeding on the progression of non-alcoholic fatty liver disease. Issue 10 (24th June 2009) - Nobili, V; Bedogni, G; Alisi, A; Pietrobattista, A; Alterio, A; Tiribelli, C; Agostoni, C
Abstract : Objective: Non-alcoholic fatty liver disease (NAFLD) is a spectrum of liver disease characterised by accumulation of large-droplet fat in hepatocytes with possible progression to inflammation and fibrosis. Breastfeeding has benefits for child health, both during infancy and later in life, reducing the risk of manifestations of the metabolic syndrome. Here we investigated the association between early type of feeding (breastfed versus formula-fed and duration of breastfeeding) and later NAFLD development. Study design: We investigated 191 young Caucasian children (3–18 years old) with NAFLD consecutively enrolled between January 2003 and September 2007 in our centre. 48% of these children (n = 91) had been breastfed for a median (interquartile range) time of 8 (7) months. Results: After correction for age, waist circumference, gestational age and neonatal weight, the odds of non-alcoholic steatohepatitis (NASH) (OR 0.04, 95% CI 0.01 to 0.10) and fibrosis (OR 0.32, 95% CI 0.16 to 0.65) were lower in breastfed versus not breastfed infants. Moreover, the odds of NASH (OR 0.70, exact 95% CI 0.001 to 0.87) and fibrosis (OR 0.86, exact 95% CI 0.75 to 0.98) decreased for every month of breastfeeding. Conclusions: This observational study suggests that earlier feeding habits might affect the clinical expression of NASH from 3 to 18 years later, with an apparent drug-like preventive effect of breastfeeding.